Phenolic and flavonoid contents in Deschampsia antarctica plants growing in nature and cultured in vitro - Maryana Twardovska; Iryna Konvalyuk; Kateryna Lystvan; Igor Andreev; Ivan Parnikoza; Viktor Kunakh (Polish Polar Research, 2021)
The paper presents data on the total phenolic and flavonoid content in Deschampsia antarctica È. Desv. plants collected from natural habitats, plants cultured in vitro, regenerated plants, and plants cultivated in a growth chamber. It was found that the shoots (aerial parts) had higher phenolic and flavonoid contents compared to the roots. The largest amount of these substances was found in wild plants from Great Yalour Island. The content of phenolics and flavonoids in plants cultured in vitro was generally comparable to that in plants collected from natural habitats except for some clones. HPLC analysis revealed five main metabolites present in similar ratios in the studied samples of wild and in vitro plants. Minor substances varied slightly in different extracts, however their presence did not depend on plant growth conditions. No significant qualitative differences in HPLC profiles were found between the wild and in vitro plants. The studied samples did not contain quercetin, kaempferol and luteolin, whereas orientin was found in all studied samples of D. antarctica.